Preventing clinically relevant pancreatic fistula with combination of linear stapling plus continuous suture of the stump in laparoscopic distal pancreatectomy - Aoki, Takeshi (BMC Surg, 2020)
BACKGROUND: Pancreatic fistula is one of the serious complications for patients undergoing distal pancreatectomy, which leads to significant morbidity. The aim of our study is to compare linear stapling closure plus continuous suture with linear stapling closure alone during laparoscopic distal pancreatectomy (LDP) in terms of clinically relevant postoperative pancreatic fistula (POPF) rate. METHODS: Twenty-two patients underwent LDP at our institution between 2011 and 2013. Twelve patients had linear stapling closure with peri-firing compression (LSC) alone compared with ten patients who had linear stapling closure, peri-firing compression plus continuous suture (LSC/CS) for stump closure of remnant pancreas in LDP. Biochemical leak and clinically relevant POPF were compared between both groups. RESULTS: POPF occurred in 4 of 12 (33.3%) patients with linear stapling closure while no patient developed a clinically relevant POPF in the triple combination of linear stapling, peri-firing compression plus continuous suture group (p = 0.043).1 patient (8.3%) in the LSC group and 5 patients (50%) in the LSC/CS group had evidence of a biochemical leak. There were no significant differences in operative time (188.3 vs 187.0 min) and blood loss (135 vs. 240 g) between both groups but there was a significantly of shorter length of hospital stay (11.9 vs. 19.9 days) in LSC/CS group (p = 0.037). There was no mortality in either group. CONCLUSIONS: The triple combination of linear stapling, peri-firing compression plus continuous suture in LDP has effectively prevented occurrence of clinically relevant ISGPF POPF. TRIAL REGISTRATION: The study was retrospectively registered September 30, 2019 at Showa University Ethics Committee as IRB protocol numbers 2943.